SINTESIS DAN KARAKTERISASI GEOPOLIMER BERBAHAN DASAR KAOLIN CAPKALA DENGAN VARIASI RASIO MOL SiO2/Al2O3 - Yatim Mustakim; Nurlina Nurlina; Intan Syahbanu (Indonesian Journal of Pure and Applied Chemistry, 2019)
One of the potential raw materials for the preparation of geopolymers is kaolin. In the present report, the used activated kaolin is from Capkala Village in West Borneo. This paper presents an experimental study on the influence of different SiO2/Al2O3 molar ratios on the compressive strength and microstructural characteristics of the Capkala kaolin-based geopolymer. The used Capkala kaolin was a product of the calcination of the source material at 750ºC 2 h. The alkaline activator solutions that were used to activate the activated capkala kaolin precursor were prepared by mixing NaOH solution with Na2SiO3 solution. The activator solution was allowed to equilibrate for a minimum of 24 h at a room temperature before use. The geopolymer was prepared by hand mixing of the Capkala kaolin and the activator solution. Experiments conducted with SiO2/Al2O3 molar ratios of 3.8; 3.9; 4.0; 4.1 and 4.2 for all mixing. The resulting pastes are cast in cylinder molds of 2.3 × 4.6 cm. The pastes hardened 24 h in the forms, at room temperature for 24 h. The geopolymer was dried at 60ºC 2 h. The geopolymer was tested for compressive strength and sample pieces were taken from ones with the highest strength for XRD and SEM. Based on the test was obtained that geopolymer with 3.9 SiO2/Al2O3 ratios has the highest compressive strength that is 2.820 Mpa. The XRD analysis showed the peak at 2θ(º) 26,69o, 20,92o dan 19,77 o. The spectra FTIR of geopolymer showed the absorption at 3289.96 cm-1; 1647.67 cm-1 and 955.65 cm-1. Moreover, there are functional groups absorption for geopolymer such Al-OH stretch vibration (near 900 cm-1), stretch vibration of Si-O and Al-O (600-700 cm-1), Si-O-Al bend vibration (near 500 cm-1). The morphology of the capkala kaolin based geopolymer with SEM has succeeded in changing the kaolin structures in the form of regular slabs to be more irregular due to heating with a temperature of 750ºC.